Post-ASPECTS based on hyperdensity in NCCT immediately after thrombectomy is an ultra-early predictor of hemorrhagic transformation and prognosis - Chen, Lulu; Xu, Ziqi; Zhang, Chen; Ji, Yachen; Huang, Xianjun; Yang, Weimin; Zhou, Zhiming; Wang, Shuiping; Wang, Kai; Luo, Benyan; Wang, Jingye (Frontiers in Neurology, 2022)
Background and Purpose: Almost half of patients exhibit futile recanalization after thrombectomy; however, the early postoperative predictors of futile recanalization remain unclear. We analyzed the relationship of post-thrombectomy ASPECTS (Post-ASPECTS) with 90-day prognosis and hemorrhagic transformation (HT). Methods: We collected data from patients with acute ischemic stroke (AIS) with anterior-circulation large vessel occlusion (ACLVO) who were treated via thrombectomy within 10 h in 3 hospitals. Successful endovascular recanalization was achieved (modified Thrombolysis in Cerebral Ischemia [mTICI] 2b/3). Non-contrast computed tomography (NCCT) examination was performed immediately (within 1 h) after thrombectomy. Post-ASPECTS were scored based on the brain parenchymal hyperdensity in NCCT according to the ASPECTS scoring method. HT was defined according to the ECASS II classification criteria. Linear correlation, logistic regression, and receiver operating characteristic curve analyses were used to determine the influencing factors and best predictive value of 90-day prognosis, 90-day death, and HT. Results: A total of 231 patients were enrolled. The good prognosis rate, mortality rate, and HT rate were 57.1%, 9.5%, and 38.3%, respectively. The Post-ASPECTS affected poor prognosis, death, and HT. The best predictive value of Post-ASPECTS for poor prognosis, death, and HT was 7. The specificities of Post-ASPECTS for predicting HT, poor prognosis, and death were 87.6% (AUC, 0.811; P < 0.001), 87.1% (AUC, 0.768; P < 0.001), and 73.7% (AUC, 0.748; P < 0.001), with positive predictive values of 74.2%, 75.7%, and 21.4%, respectively. Conclusions: Post-ASPECTS predicted 90-day prognosis, death, and HT with high specificity and high positive predictive value in patients with AIS with ACLVO. Post-ASPECTS may be an ultra-early predictor of prognosis after thrombectomy.